1997
DOI: 10.1016/s0022-5223(97)70147-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemotherapy versus surgical therapy alone for squamous cell carcinoma of the esophagus: A prospective randomized trial

Abstract: Preoperative chemotherapy was safe and resulted in significant downstaging and an increased likelihood of curative resection. Survival was not better than that in the surgery-alone group, but responders did fare better than nonresponders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
173
0
17

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(196 citation statements)
references
References 15 publications
6
173
0
17
Order By: Relevance
“…Several studies looking at neoadjuvant and palliative chemotherapy reported that those patients who responded to treatment had an improved survival outcome [4][5][6][7][8][9] with neo-adjuvant regimens having a response rate, at best, of 50-60% [1]. Studies clearly demonstrate that those who do not respond to neoadjuvant chemotherapy have a significantly worse prognosis than those who have surgery alone [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies looking at neoadjuvant and palliative chemotherapy reported that those patients who responded to treatment had an improved survival outcome [4][5][6][7][8][9] with neo-adjuvant regimens having a response rate, at best, of 50-60% [1]. Studies clearly demonstrate that those who do not respond to neoadjuvant chemotherapy have a significantly worse prognosis than those who have surgery alone [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies clearly demonstrate that those who do not respond to neoadjuvant chemotherapy have a significantly worse prognosis than those who have surgery alone [4,5,7]. If outcome is to be maximised in patients likely to derive benefits from neoadjuvant therapy while at the same time ensuring others are not subjected to potentially harmful and ineffectual treatment, an early means of differentiating responders from non responders is required.…”
Section: Introductionmentioning
confidence: 99%
“…1 Esophagectomy is the treatment of choice in patients with early-stage disease. In patients with more advanced stage disease, the role of neoadjuvant therapy before esophagectomy is evolving, [2][3][4][5][6][7] with most studies showing no benefit over surgery alone. 6,7 However, there is evidence to suggest that the subset of patients who have a pathological response to neoadjuvant therapy will have improved survival after surgery compared with those patients who undergo esophagectomy alone.…”
mentioning
confidence: 99%
“…In patients with more advanced stage disease, the role of neoadjuvant therapy before esophagectomy is evolving, [2][3][4][5][6][7] with most studies showing no benefit over surgery alone. 6,7 However, there is evidence to suggest that the subset of patients who have a pathological response to neoadjuvant therapy will have improved survival after surgery compared with those patients who undergo esophagectomy alone. 5,6,[8][9][10][11] Conversely, patients who do not have a pathological response to neoadjuvant therapy have a worse prognosis after subsequent esophagectomy than those patients who are resected de novo.…”
mentioning
confidence: 99%
See 1 more Smart Citation